Kanji Learning for Japanese Language Learners with `Phyctograph' Memory Strategy - Lensun, Sherly Ferro; Aror, Susanti; Sompotan, Amelia; Pandi, Helena (KnE Social Sciences, 2024)
The choice of teaching and studying strategies for language gaining knowledge of strategies have to be primarily based on the consideration of putting students as learning topics who no longer do what is conveyed by the educator. Coaching Japanese especially kanji through the usage of diverse learning strategies makes it easier for Japanese language learners, mainly in mastering Japanese letters/kanji. The mastering strategy used is an instantaneous method and an oblique method. Direct strategy is an approach, this is directly associated with foreign language mastering. It is directly associated with language in numerous obligations and situations, which include (1) reminiscence strategies, (2) cognitive strategies, and (3) compensation strategies. Letters are a very important thing in learning Japanese because Japanese has very complex writing. A kanji can convey many meanings, therefore it is said that the number of kanji is almost the same as the number of objects in the world. To minimize the difficulty in learning kanji, ways to understand meaning through its constituent elements are needed, namely: Recognizing the pictography and the kanji parts (bushu部首), for example, the character kuchihen (口) which is a symbol related to the mouth or lips. This kanji when combined with other characters can form meanings related to the mouth, lips, or speech. Pictographs are signs in the form of pictures in the ancient writing system. So, with pictographs you can find out how the kanji really is and can imagine the real form of the kanji. This research was conducted with the experimental method. The grouping of subjects was done randomly. The study’s layout used is the one organization Pre-test and put up-check design (one institution Pre-take a look at submit-check). This layout consists of an unmarried institution that acts as an experimental magnificence, this is given a preliminary check (pre-take a look at) earlier than remedy and a final test (post-check) after treatment. The results of the t-test obtained were quite top results, namely the value of t = 1,945. This end result as compared with the t-value inside the t-distribution table, which is 1,729, means that it is acceptable to say that there has been a change and an increase in students’ understanding of kanji. Thus, the effectiveness of the use of pictograph media has been well-tested. Keywords: Memory strategy, kanji, Japanese, learning, phyctograph